2020
DOI: 10.1101/2020.04.20.050914
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibiotic-resistantSalmonella speciesandEscherichia coliin broiler chickens from farms, abattoirs and open markets in selected districts of Zambia

Abstract: 30Salmonella species and Escherichia coli are major bacterial enteropathogens of global 31 public health importance that cause foodborne diseases, thereby contributing to increased 32 human morbidity and mortality. Both pathogens have also been found to contribute towards 33 the spread of antimicrobial resistance through the food chain, especially in poultry. The aim of 34 this study was to determine the occurrence of antibiotic-resistant Salmonella sp. and E. coli in 35 broiler chickens at farm level, abat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(45 reference statements)
1
3
0
Order By: Relevance
“…In this study, the highest multi-drug resistance (MDR) was observed to the following antibiotics ampicillin, tetracycline, and trimethoprim/sulfamethoxazole. These findings were in agreement with other studies done in Iran, USA, India, Brazil, Thailand, and Southern African, [1,16,36,[43][44][45] that revealed MDR in Enterobacteriaceae, including Salmonella spp. and E. coli.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, the highest multi-drug resistance (MDR) was observed to the following antibiotics ampicillin, tetracycline, and trimethoprim/sulfamethoxazole. These findings were in agreement with other studies done in Iran, USA, India, Brazil, Thailand, and Southern African, [1,16,36,[43][44][45] that revealed MDR in Enterobacteriaceae, including Salmonella spp. and E. coli.…”
Section: Discussionsupporting
confidence: 93%
“…This is similar to what was reported in India in which resistance was 18% amoxicillin-clavulanic acid, 18% ampicillin, 20% cefotaxime [36] and those reported in the United States in which they found the resistance of 1% amoxicillin-clavulanic acid, 26% ampicillin, and 0% Ceftriaxone. [16] The frequency and extent of Salmonella spp. resistance to antimicrobial drugs varies based on their usage in animal production and humans as well as on ecological differences in the epidemiology of Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chicken population is estimated to be 94 million broilers, 15 million village chickens, and 5.8 million layers [1]. Moreover, poultry products in Zambia, like in other developing African countries, form an integral part of the human diet in many households, as they are cheaper source of animal protein and are easier to produce compared with other foods of animal origin [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The chicken population is estimated at 94 million broilers,15 million village chickens, and 5.8 million layers [1]. Moreover, poultry products in Zambia, like in other developing African countries, form an integral part of the human diet in many households, as it is a cheaper source of animal protein and is easier to produce compared to other foods of animal origin [2,3].…”
Section: Introductionmentioning
confidence: 99%